Quality evaluation of Buffalo meatballs produced at different comminution process temperatures - Jwee Yie, Lim; Khalid, Nurul Izzah; Ismail-Fitry, Mohammad Rashedi (Penerbit UTM Press, 2023)
Buffalo meatballs were formulated and the effects of different comminution temperatures on the quality (cooking yield, water holding capacity (WHC), protein, texture, colour, and sensory) were evaluated. During the mixing of ingredients, the comminution temperature was adjusted using different types of water which were ice (0°C), ice water (4°C), cold water (10°C), room temperature water (22°C), and warm water (32°C). Following comminution for 3 minutes, the temperatures of the batters were recorded at 14, 25, 25, 29, and 27°C, respectively. The comminution took a total of 15 minutes had produced batters with similar final temperatures (ranging from 36 to 38°C), except ice temperature mixing (28°C). Cold water meatballs produced the highest cooking yield but significantly the lowest (P<0.05) water-holding capacity. The colour of the cold water meatball shows significantly (P<0.05) the highest L* (lightness), significantly (p<0.05) the lowest a* (redness), and the lowest b* (yellowness) values. While the textures (hardness, cohesiveness, gumminess, chewiness, and springiness) of all meatballs were similar (P>0.05). All meatball samples had nearly similar soluble protein concentrations (0.97 to 1.06 ug/ml) but ice water meatballs had the highest (P<0.05). The panellists gave all the meatballs a score ranging from 6.32 to 6.98, with ice meatballs receiving the highest mean score (6.98) acceptability score (P>0.05). In conclusion, comminuted buffalo meatballs can be produced using either ice, ice water, cold water, room temperature water, or warm water without affecting their quality. However, ice is suggested for safety purposes against microbial growth during processing.